Mapping Studies on Risk and Protective Factors for Mental Health in the Modern Era - Dito Anurogo; Yocki Yuanti; Sri Kubillawati; Emdat Suprayitno; Gamar Abdullah (Westscience Press, 2024)
This bibliometric study delves into the extensive literature on risk and protective factors for mental health in the modern era, considering the complexities posed by technological advancements, socio-cultural shifts, and globalization. Utilizing bibliometric analysis, we identify clusters of literature, analyze trends over time, and explore potential research avenues. The network visualization reveals six distinct clusters, each representing thematic discussions related to mental health. Trend analysis highlights the evolution of research focus from early concerns to contemporary issues, with COVID-19 emerging as a prominent theme. Density analysis identifies research gaps and potential future topics. The collaboration network among authors suggests opportunities for interdisciplinary research. This analysis offers valuable insights for researchers, policymakers, and practitioners to inform evidence-based strategies for navigating the intricate landscape of mental health in the modern era.